The Future of Security? Surveillance Operations at Homeland Security Fusion Centers - Monahan, Torin (Social justice, 2010)
The article focuses on the counterterrorist fusion centers of the U.S. Department of Homeland Security in U.S. states during the administration of U.S. President Barack Obama. Topics include the increase of state-controlled surveillance operations, perceptions in the U.S. about the security measures of the fusion centers, and abuses and scandals involving fusion centers in racist practices and illegal infiltration of peaceful groups. It is suggested that state agencies and law enforcement officials break the law in data and surveillance collection for counterrrorism in the fusion centers and should practice more democratic measures.